Polyether sulfone and a method for producing the same
Patent Information
- Application Number
- CN202511149286.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2025-06-18
- Filing Date
- 2025-08-18
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2045-08-18
AI Technical Summary
[0004]然而,正是这种高度的结构规整性,也成为了限制PES进一步发展的瓶颈
[0020]1.本发明将严格控制添加量的联苯二酚部分替代双酚S,引入聚醚砜分子链段中,并采用阶段补加的方式将4,4'-二氟二苯砜部分替代4,4'-二氯二苯砜作为活性补偿单体,纳米碳酸钙作为捕获剂和调节剂,最终制备得到聚醚砜。本发明制备的聚醚砜成品中小分子杂质少,在不影响聚醚砜原本整体结构性能和反应活性的基础上,通过联苯二酚刚性结构的引入,小幅提高了聚醚砜的热性能,改善了力学性能,提高聚醚砜树脂本身的可加工性;同时,通过4,4'-二氟二苯砜补偿聚合反应活性,通过纳米碳酸钙维持体系内pH环境、调控反应速率、调控部分聚醚砜分子链有序排列,提高力学性能和热性能,抑制高温时发生的交联或支化反应,并捕获可能由于副反应而产生的微量HF。本发明制备的聚醚砜可以在应用于膜领域的同时,扩展应用于耐高负荷、耐高温的航空航天部件、医疗器械、深海设备等高附加值领域。
Smart Images

Figure CN121136086B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of resin technology, specifically to polyethersulfone and its preparation method. Background Technology
[0002] Polyethersulfone (PES) is a class of amorphous high-performance engineering plastics with sulfone groups and ether bonds in its main chain. It is synthesized from bisphenol monomers and dihalodiphenyl sulfones via a nucleophilic aromatic substitution reaction. Its unique chemical structure endows it with excellent high-temperature resistance, mechanical strength, and chemical stability, and it is widely used in medical devices, electronic packaging, water treatment membranes, and other fields.
[0003] The conventional synthesis process for PES involves the reaction of bisphenol S with 4,4'-dichlorodiphenyl sulfone. In this process, bisphenol S, containing active hydrogen atoms, acts as a nucleophile, attacking the halogen atoms on 4,4'-dichlorodiphenyl sulfone to gradually form a long-chain polymer. This classic synthetic route is quite mature. By precisely controlling reaction conditions, such as monomer ratio, reaction temperature, and time, PES with highly regular structures can be prepared (e.g., a method for synthesizing polyethersulfone resin disclosed in Chinese invention patent CN106565957A). This regularity directly brings many advantages: First, the material exhibits extremely high thermal stability, capable of operating for extended periods in harsh high-temperature environments without significant degradation; second, its chemical stability is equally excellent, showing good resistance to various organic solvents and acid / alkali media; third, due to its regular molecular chain and low crystallinity, its processing performance is relatively controllable, allowing it to be molded through various methods such as injection molding, extrusion, casting, and spinning.
[0004] However, this very high structural regularity has also become a bottleneck restricting the further development of PES. On the one hand, the regular chain structure makes sliding between molecular chains difficult, resulting in relatively insufficient toughness of the material, especially prone to brittle fracture under impact or stress. On the other hand, the single structure also means that its functionality is relatively limited, making it difficult to meet the additional performance requirements of certain specific applications. These limitations mean that although PES has a wide range of applications, it is mainly concentrated in fields with high requirements for temperature resistance, chemical stability, and film-forming properties, such as medical devices (e.g., hemodialysis membranes, filters), electronic packaging (chip substrates), and water treatment membranes (used for drinking water purification and industrial wastewater treatment). Its application in high-value-added fields such as high-load, high-temperature resistant structural components is relatively limited.
[0005] Based on a profound understanding of the limitations of existing PES materials and a desire for broader applications, developing a novel method for preparing polyethersulfone is particularly important and urgent. This innovative method does not aim to overturn the basic structure of PES, but rather to refine it, "upgrading" and "optimizing" its performance while preserving as much of its original excellent properties as possible (such as high heat resistance, good chemical stability, and controllable processability). This will improve its thermal, mechanical, and processability properties, enabling PES to be applied not only in the membrane field but also in high-value-added fields such as high-load, high-temperature components. Summary of the Invention
[0006] The technical problem to be solved by the present invention is to overcome the shortcomings of the prior art, provide polyethersulfone and its preparation method, and further improve the thermal properties, mechanical properties and processability of polyethersulfone while retaining the original excellent properties of polyethersulfone, and further expand the application fields of polyethersulfone.
[0007] The technical solution of this invention is as follows:
[0008] On one hand, the present invention provides a method for preparing polyethersulfone, comprising the following steps:
[0009] Preparation of S1 polyethersulfone polymerization solution: Under a nitrogen atmosphere, using N-methylpyrrolidone (NMP) as solvent, biphenyl (BP), bisphenol S (BPS), and a salt-forming agent were added to a reaction vessel and stirred. The temperature was raised to 120-140℃ for a salt-forming reaction for 1-2 hours. Then, the temperature was raised to 130-150℃, and an N-methylpyrrolidone solution of 4,4'-difluorodiphenyl sulfone (DFDPS) was added and collected. After collection, nano-calcium carbonate was added, and then the temperature was raised to 180-200℃, and N-methylpyrrolidone solution of 4,4'-dichlorodiphenyl sulfone (DCDPS) was added. The methylpyrrolidone solution was collected and the reaction continued until the reaction was completed. Then, after dilution, cooling, and end-capping, a polyethersulfone polymer solution was obtained. The proportions of biphenyl alcohol to the total molar amount of biphenyl alcohol and bisphenol S and the proportions of 4,4'-difluorodiphenyl sulfone to the total molar amount of 4,4'-difluorodiphenyl sulfone and 4,4'-dichlorodiphenyl sulfone were the same, both <8%, and the ratio of the total molar amount of biphenyl alcohol and bisphenol S, the total molar amount of 4,4'-difluorodiphenyl sulfone and 4,4'-dichlorodiphenyl sulfone, and the molar amount of salt-forming agent was 1:1:(1.03-1.07).
[0010] S2 post-processing: After dilution, the polyethersulfone polymer solution undergoes adsorption treatment, filtration, crushing, classification washing, and drying to obtain polyethersulfone.
[0011] Preferably, in step S1, the salt-forming agent is potassium carbonate; the mass ratio of nano-calcium carbonate to biphenyl is (0.1-0.3):100.
[0012] Preferably, in step S1, after the reaction is completed and before dilution and cooling, the solid-liquid ratio of the system is (0.96-1.04):1.
[0013] Preferably, in step S1, the method of adding 4,4'-difluorodiphenyl sulfone is as follows: 4,4'-difluorodiphenyl sulfone is dissolved in N-methylpyrrolidone to obtain a solution, and the solution is added to the reactor at a uniform rate to participate in the reaction. The solution temperature is 70-100℃, and the addition and extraction time is 0.5-1.5h. The method of adding 4,4'-dichlorodiphenyl sulfone is as follows: 4,4'-dichlorodiphenyl sulfone is dissolved in N-methylpyrrolidone to obtain a solution, and the solution is added to the reactor at a uniform rate to participate in the reaction. The solution temperature is 120-150℃, and the addition and extraction time is 1-2h. After the 4,4'-dichlorodiphenyl sulfone is extracted, the water content of N-methylpyrrolidone in the reactor is ≤0.03wt.%.
[0014] Preferably, in step S1, after the reaction is complete, N-methylpyrrolidone is added for dilution and cooling, and the mass ratio of the N-methylpyrrolidone used to the existing N-methylpyrrolidone in the system is 1:(1-1.2); an end-capping agent is added for end-capping, and the end-capping agent is chloromethane, 4-phenylethynyl-3-trifluoromethylaniline or 4-fluorobenzophenone, and the molar ratio of the end-capping agent to the uncapped polyethersulfone is (0.01-0.1):1.
[0015] Preferably, in step S2, an adsorbent is added to adsorb the polyethersulfone polymer solution. The adsorbent is nano-alumina, and its molar ratio with the final polyethersulfone is (0.3-0.5):100. After adding the adsorbent, the mixture is stirred for 1-2 hours at a temperature of 20-40°C. The mixture is then filtered using filter paper or filter cloth with a pore size of 5-20 μm.
[0016] Preferably, in step S2, the graded washing process is as follows: first, wash once with an 8-15 wt.% N-methylpyrrolidone aqueous solution for 3 hours at a temperature of 80-100°C; then wash twice with a 10-30 wt.% ethanol aqueous solution for 1 hour each time at a temperature of 50-70°C; finally, wash three times with deionized water for 1 hour each time at a temperature of 90-100°C.
[0017] Preferably, in step S2, the drying temperature is 110-130℃, and the fluorine content of the polyethersulfone obtained after drying is <1ppm.
[0018] On the other hand, the present invention provides polyethersulfone, which is prepared by the above-described method for preparing polyethersulfone.
[0019] Compared with the prior art, the present invention has the following advantages:
[0020] 1. This invention involves the partial replacement of bisphenol S with biphenyl sulfone (BPS) in strictly controlled amounts, introducing it into the polyethersulfone (PES) molecular chain. Furthermore, 4,4'-difluorodiphenyl sulfone (4,4'-dichlorodiphenyl sulfone) is partially replaced as an activity-compensating monomer using a staged addition method. Nano-calcium carbonate serves as a trapping agent and regulator, ultimately yielding PES. The PES product prepared by this invention has fewer small-molecule impurities. Without affecting the original overall structure, performance, and reactivity of PES, the introduction of the rigid structure of biphenyl sulfone slightly improves the thermal and mechanical properties of PES, enhancing the processability of the PES resin itself. Simultaneously, by compensating for polymerization reactivity with 4,4'-difluorodiphenyl sulfone, and by maintaining the pH environment, regulating the reaction rate, and controlling the ordered arrangement of some PES molecular chains using nano-calcium carbonate, mechanical and thermal properties are improved. Crosslinking or branching reactions occurring at high temperatures are suppressed, and trace amounts of HF that may be generated due to side reactions are captured. The polyethersulfone prepared by this invention can be applied not only in the membrane field, but also in high-value-added fields such as aerospace components, medical devices, and deep-sea equipment that are resistant to high loads and high temperatures.
[0021] 2. This invention employs a staged reaction, staged heating, and graded sampling and replenishment polymerization method, ensuring the full progress of each stage of the reaction, resulting in higher polymerization degree and purity of polyethersulfone (PES), and greater applicability. The invention utilizes pre-polymerization capture, post-polymerization multiple adsorption, and graded washing to ensure that the trace amounts of HF generated during the sampling and replenishment of 4,4'-difluorodiphenyl sulfone and the polymerization stage, which may be due to side reactions, are fully captured, adsorbed, and recovered, avoiding equipment corrosion. Simultaneously, it can gradually remove residual salts, halide ions, metal particles, and NMP from the PES, resulting in fewer residual impurities and higher light transmittance in the final PES. Furthermore, the addition of 4,4'-difluorodiphenyl sulfone can reduce energy consumption, decrease high-temperature side reactions (such as crosslinking and oxidation), improve thermal performance, enhance the dielectric properties of PES, and reduce surface energy, making it suitable for applications in high-frequency electronic packaging materials and anti-fouling coatings. Attached Figure Description
[0022] Figure 1 This is the infrared spectrum of the polyethersulfone prepared in Example 1 of this invention. Detailed Implementation
[0023] To enable those skilled in the art to better understand the technical solutions of this invention, the technical solutions of this invention will be clearly and completely described below in conjunction with the embodiments of this invention.
[0024] Example 1
[0025] The preparation method of polyethersulfone in this embodiment includes the following steps:
[0026] Preparation of S1 polyethersulfone polymerization solution: Nitrogen gas was introduced into the reactor. Using 539 mL of NMP as solvent, 237.757 g BPS, 9.311 g BP, and 145.116 g potassium carbonate were added to the reactor and stirred. The temperature was raised to 130 °C, and the salt formation reaction was carried out for 1.5 h. Then the temperature was raised to 140 °C, and at this time, an NMP solution containing 12.713 g DFDPS at 80 °C was added at a uniform rate and collected. The collection and addition time was 1 h. After the collection was completed, 18.622 mg of nano calcium carbonate was added, and then the temperature was raised to 190 °C. At this time, an NMP solution containing 272.802 g DCDPS at 140 °C was added at a uniform rate and collected. The collection and addition time was 1.5 h. The total amount of NMP added during the whole process was 280 mL, and the total amount of NMP collected was 368 mL. At this point, the water content of NMP in the reactor was 0.02 wt.%, and the reaction continued until completion, at which point the solid-liquid ratio of the system was 1:1. Subsequently, 1.1 times the mass of existing NMP in the system was added for dilution and cooling, and then chloromethane gas was introduced for end-capping to obtain a polyethersulfone polymer solution, wherein the molar ratio of chloromethane gas to uncapped polyethersulfone was 0.05:1.
[0027] S2 Post-treatment: The polyethersulfone polymerization solution was diluted and then subjected to adsorption treatment with nano-alumina. Stirring was continued for 1.5 hours at 30°C, with a molar ratio of nano-alumina to the final polyethersulfone of 0.4:100. The mixture was then filtered through 10 μm filter paper and crushed. The crushed polyethersulfone powder was washed with a 10 wt.% NMP aqueous solution at 90°C for 3 hours, followed by two washes with a 20 wt.% ethanol aqueous solution at 60°C for 1 hour each, and finally three washes with deionized water at 100°C for 1 hour each. After washing, the powder was dried at 120°C for 12 hours to obtain the final polyethersulfone. The fluorine content of the polyethersulfone prepared in this example was determined to be 0.4 ppm by potentiometric titration.
[0028] The infrared spectrum of the polyethersulfone prepared in this embodiment is as follows: Figure 1 As shown, it can be seen at 1483.59cm -1 1319.7cm -1 1231.77cm -1 1144.3cm -1 The presence of distinct characteristic peaks belonging to polyethersulfone at all locations indicates that polyethersulfone was successfully prepared in this embodiment.
[0029] Example 2
[0030] The preparation method of polyethersulfone in this embodiment includes the following steps:
[0031] Preparation of S1 polyethersulfone polymerization solution: Nitrogen gas was introduced into the reactor. Using 539 mL of NMP as solvent, 233.052 g BPS, 5.363 g BP, and 136.658 g potassium carbonate were added to the reactor and stirred. The temperature was raised to 120 °C, and the salt formation reaction was carried out for 1 h. Then the temperature was raised to 130 °C, and at this time, an NMP solution containing 7.322 g DFDPS at 70 °C was added at a uniform rate and collected. The collection and addition time was 0.5 h. After the collection was completed, 5.363 mg of nano calcium carbonate was added, and then the temperature was raised to 180 °C. At this time, an NMP solution containing 267.403 g DCDPS at 120 °C was added at a uniform rate and collected. The collection and addition time was 1 h. The total amount of NMP added during the whole process was 280 mL, and the total amount of NMP collected was 368 mL. At this point, the water content of NMP in the reactor was 0.03 wt.%, and the reaction continued until completion, at which point the solid-liquid ratio of the system was 0.96:1. Subsequently, an equal mass of NMP was added to dilute and cool the system, and then 4-fluorobenzophenone was introduced for end-capping to obtain a polyethersulfone polymerization solution, wherein the molar ratio of 4-fluorobenzophenone to uncapped polyethersulfone was 0.01:1.
[0032] S2 Post-treatment: The polyethersulfone polymerization solution was diluted and then subjected to adsorption treatment with nano-alumina. Stirring was continued for 1 hour at 20°C, with a molar ratio of nano-alumina to the final polyethersulfone of 0.3:100. The mixture was then filtered through 5μm filter paper and crushed. The crushed polyethersulfone powder was washed with a 15wt.% NMP aqueous solution at 80°C for 3 hours, followed by two washes with a 10wt.% ethanol aqueous solution at 50°C for 1 hour each, and finally three washes with deionized water at 90°C for 1 hour each. After washing, the powder was dried at 110°C for 12 hours to obtain the final polyethersulfone. The fluorine content of the polyethersulfone prepared in this example was determined to be 0.7 ppm by potentiometric titration.
[0033] Example 3
[0034] The preparation method of polyethersulfone in this embodiment includes the following steps:
[0035] Preparation of S1 polyethersulfone polymerization solution: Nitrogen gas was introduced into the reactor. Using 539 mL of NMP as solvent, 242.062 g BPS, 13.556 g BP, and 153.796 g potassium carbonate were added to the reactor and stirred. The temperature was raised to 140 °C, and the salt formation reaction was carried out for 2 h. Then the temperature was raised to 150 °C, and at this time, an NMP solution containing 18.509 g DFDPS at 100 °C was added at a uniform rate and collected. The collection and addition time was 1.5 h. After the collection was completed, 40.668 mg of nano calcium carbonate was added, and then the temperature was raised to 200 °C. At this time, an NMP solution containing 277.741 g DCDPS at 150 °C was added at a uniform rate and collected. The collection and addition time was 2 h. The total amount of NMP added during the whole process was 280 mL, and the total amount of NMP collected was 368 mL. At this point, the water content of NMP in the reactor was 0.01 wt.%, and the reaction continued until completion, at which point the solid-liquid ratio of the system was 1.04:1. Subsequently, 1.2 times the mass of the existing NMP in the system was added for dilution and cooling, and then 4-phenylethynyl-3-trifluoromethylaniline was introduced for end-capping to obtain a polyethersulfone polymerization solution, wherein the molar ratio of 4-phenylethynyl-3-trifluoromethylaniline to uncapped polyethersulfone was 0.1:1.
[0036] S2 Post-treatment: The polyethersulfone polymerization solution was diluted and then subjected to adsorption treatment with nano-alumina. Stirring was continued for 2 hours at 40°C, with a molar ratio of nano-alumina to the final polyethersulfone of 0.5:100. The mixture was then filtered through 20μm filter paper and crushed. The crushed polyethersulfone powder was washed with 8wt.% NMP aqueous solution at 100°C for 3 hours, followed by washing twice with 30wt.% ethanol aqueous solution at 70°C for 1 hour each time, and finally washed three times with deionized water at 95°C for 1 hour each time. After washing, the powder was dried at 130°C for 12 hours to obtain the final polyethersulfone. The fluorine content of the polyethersulfone prepared in this example was determined to be 0.9 ppm by potentiometric titration.
[0037] Comparative Example 1
[0038] The difference from Example 1 is that in step S1, BPS is used in equimolar form instead of BP.
[0039] Comparative Example 2
[0040] The difference from Example 1 is that in step S1, DCDPS is used in equimolar form instead of DFDPS.
[0041] Comparative Example 3
[0042] The difference from Example 1 is that in step S1, the amount of BP added is 18.621g, the amount of BPS added is 225.243g, the amount of DCDPS added is 258.444g, and the amount of DFDPS added is 25.425g.
[0043] Comparative Example 4
[0044] The difference from Example 1 is that in step S1, the amount of BP added is 9.311g, the amount of BPS added is 233.052g, the amount of DCDPS added is 275.674g, and the amount of DFDPS added is 10.17g.
[0045] Comparative Example 5
[0046] The difference from Example 1 is that no nano-calcium carbonate is added in step S1.
[0047] Comparative Example 6
[0048] The difference from Example 1 is that in step S1, after the salt formation reaction, the temperature is directly raised to 190°C, and NMP solution of DFDPS and DCDPS at 140°C is added at a constant rate and then collected. The collection and replenishment time is 2.5h.
[0049] Comparative Example 7
[0050] The difference from Example 1 is that no adsorption treatment is performed in step S2.
[0051] The performance of the polyethersulfones prepared in Examples 1-3 and Comparative Examples 1-7 was tested:
[0052] (1) Thermal properties: The glass transition temperature (T) of each polyethersulfone sample was measured. g ).
[0053] (2) Mechanical properties: Each polyethersulfone sample was prepared into specimens, and the mechanical properties of each specimen were tested. The test methods are as follows: tensile strength and tensile modulus were tested according to GB / T 1040.2-2006 Determination of tensile properties of plastics; flexural strength and flexural modulus were tested according to GB / T 9341-2008 Determination of flexural properties of plastics; notched impact strength of cantilever beam was tested according to GB / T 1843-2008 Determination of impact strength of cantilever beam of plastics; notched impact strength of simply supported beam was tested according to GB / T 1043.1-2008 Determination of impact properties of simply supported beam of plastics.
[0054] (3) Transmittance: Each polyethersulfone sample was made into a 2mm thick polyethersulfone plate of the same specifications, and the transmittance of each plate was tested using a transmittance tester.
[0055] The performance test results of the polyethersulfones prepared in Examples 1-3 and Comparative Examples 1-7 are shown in Table 1:
[0056] Table 1. Performance test results of polyethersulfone prepared in Examples 1-3 and Comparative Examples 1-7
[0057]
[0058] As shown in Table 1, Example 1, by partially replacing bisphenol S with biphenyl phenol and partially replacing 4,4'-dichlorodiphenyl sulfone with 4,4'-difluorodiphenyl sulfone as the reactivity-compensating monomer, demonstrates a synergistic effect between biphenyl phenol and 4,4'-difluorodiphenyl sulfone, resulting in superior thermal and mechanical properties of the polyethersulfone sample without affecting polymerization efficiency. Comparative Example 1, however, did not include biphenyl phenol, thus failing to introduce a rigid structure into the polyethersulfone. Comparative Example 2, also lacking 4,4'-difluorodiphenyl sulfone, neither compensated for reactivity nor synergistically improved the performance of the polyethersulfone with biphenyl phenol, leading to a decrease in the thermal and mechanical properties of the polyethersulfone prepared in Comparative Examples 1 and 2. Therefore, it is evident that biphenyl phenol and 4,4'-difluorodiphenyl sulfone must be used simultaneously; otherwise, the technical effect of Example 1 cannot be achieved.
[0059] Compared to Example 1, the polyethersulfones prepared in Comparative Examples 3 and 4 showed relatively poor performance, indicating that the amount and ratio of biphenylene glycol and 4,4'-difluorodiphenyl sulfone added both affect the performance of polyethersulfone. Specifically, excessive addition of biphenylene glycol can cause the overall structure of the polyethersulfone to lean towards polyphenylene sulfone; while an unequal ratio of biphenylene glycol and 4,4'-difluorodiphenyl sulfone will result in insufficient compensating activity, affecting the reaction efficiency and degree, and thus impacting the performance of the polyethersulfone.
[0060] As can be seen from Example 1 and Comparative Example 5, nano-calcium carbonate is crucial as a capture agent and regulator. It maintains the pH environment in the system, regulates the reaction rate, regulates the orderly arrangement of some polyethersulfone molecular chains, and inhibits the cross-linking or branching reaction that occurs at high temperature, thereby improving the polymerization effect and resulting in polyethersulfone with better performance.
[0061] As demonstrated in Example 1 and Comparative Example 6, 4,4'-difluorodiphenyl sulfone undergoes self-decomposition at excessively high reaction temperatures, releasing HF. Furthermore, the decomposition products may participate in side reactions, leading to molecular chain termination and affecting the final polyethersulfone performance. Therefore, the entire polymerization process should employ staged heating and phased addition of 4,4'-difluorodiphenyl sulfone and 4,4'-dichlorodiphenyl sulfone to avoid the aforementioned effects caused by excessively high temperatures.
[0062] As can be seen from Example 1 and Comparative Example 7, adsorption treatment of polyethersulfone polymer solution can effectively remove impurities generated in polyethersulfone and improve the light transmittance of polyethersulfone.
[0063] In summary, this invention utilizes biphenyl hydroquinone to partially replace bisphenol S, and 4,4'-difluorodiphenyl sulfone to partially replace 4,4'-dichlorodiphenyl sulfone as an active compensation monomer. Nano-calcium carbonate is used as a trapping agent and regulator. A staged heating and fractional extraction and replenishment method is employed to efficiently condense polyethersulfone in an N-methylpyrrolidone solvent system. This results in polyethersulfone possessing superior thermal, mechanical, and processing properties. While its application in the membrane field can be expanded to high-value-added fields such as high-load, high-temperature resistant aerospace components, medical devices, and deep-sea equipment, it can also be applied to other areas.
Claims
1. A method for preparing polyethersulfone, characterized in that, Includes the following steps: Preparation of S1 polyethersulfone polymerization solution: Under a nitrogen atmosphere, using N-methylpyrrolidone as a solvent, biphenyl hydroquinone, bisphenol S, and a salt-forming agent were added to a reaction vessel and stirred. The temperature was raised to 120-140℃ for a salt-forming reaction for 1-2 hours. Then, the temperature was raised to 130-150℃, and a solution of 4,4'-difluorodiphenyl sulfone in N-methylpyrrolidone was added and collected. After collection, nano-calcium carbonate was added, and then the temperature was raised to 180-200℃, and a solution of 4,4'-dichlorodiphenyl sulfone in N-methylpyrrolidone was added and collected. After completion, the reaction continues until the reaction is finished; then, after dilution, cooling, and end-capping, a polyethersulfone polymer solution is obtained; wherein, the proportion of biphenyl alcohol to the total molar amount of biphenyl alcohol and bisphenol S and the proportion of 4,4'-difluorodiphenyl sulfone to the total molar amount of 4,4'-difluorodiphenyl sulfone and 4,4'-dichlorodiphenyl sulfone are the same, both <8%, and the ratio of the total molar amount of biphenyl alcohol and bisphenol S, the total molar amount of 4,4'-difluorodiphenyl sulfone and 4,4'-dichlorodiphenyl sulfone, and the molar amount of salt-forming agent is 1:1:(1.03-1.07); S2 post-processing: After dilution, the polyethersulfone polymer solution undergoes adsorption treatment, filtration, crushing, classification washing, and drying to obtain polyethersulfone.
2. The method for preparing polyethersulfone according to claim 1, characterized in that, In step S1, the salt-forming agent is potassium carbonate; the mass ratio of nano-calcium carbonate to biphenyl is (0.1-0.3):
100.
3. The method for preparing polyethersulfone according to claim 1, characterized in that, In step S1, the addition of 4,4'-difluorodiphenyl sulfone is as follows: 4,4'-difluorodiphenyl sulfone is dissolved in N-methylpyrrolidone to obtain a solution, and the solution is added to the reactor at a uniform rate to participate in the reaction. The solution temperature is 70-100℃, and the addition and extraction time is 0.5-1.5h. The addition of 4,4'-dichlorodiphenyl sulfone is as follows: 4,4'-dichlorodiphenyl sulfone is dissolved in N-methylpyrrolidone to obtain a solution, and the solution is added to the reactor at a uniform rate to participate in the reaction. The solution temperature is 120-150℃, and the addition and extraction time is 1-2h. After the 4,4'-dichlorodiphenyl sulfone is extracted, the water content of N-methylpyrrolidone in the reactor is ≤0.03wt.%.
4. The method for preparing polyethersulfone according to claim 1, characterized in that, In step S1, after the reaction is complete, N-methylpyrrolidone is added for dilution and cooling. The mass ratio of the N-methylpyrrolidone used to the existing N-methylpyrrolidone in the system is 1:(1-1.2). An end-capping agent is added for end-capping. The end-capping agent is chloromethane, 4-phenylethynyl-3-trifluoromethylaniline or 4-fluorobenzophenone. The molar ratio of the end-capping agent to the uncapped polyethersulfone is (0.01-0.1):
1.
5. The method for preparing polyethersulfone according to claim 1, characterized in that, In step S2, an adsorbent is added to adsorb the polyethersulfone polymer solution. The adsorbent is nano-alumina, and its molar ratio with the final polyethersulfone is (0.3-0.5):
100. After adding the adsorbent, the mixture is stirred for 1-2 hours at a temperature of 20-40℃. The mixture is then filtered using filter paper or filter cloth with a pore size of 5-20μm.
6. The method for preparing polyethersulfone according to claim 1, characterized in that, In step S2, the graded washing process is as follows: first, wash once with an 8-15 wt.% N-methylpyrrolidone aqueous solution for 3 hours at a temperature of 80-100℃; then wash twice with a 10-30 wt.% ethanol aqueous solution for 1 hour each time at a temperature of 50-70℃; finally, wash three times with deionized water for 1 hour each time at a temperature of 90-100℃.
7. The method for preparing polyethersulfone according to claim 1, characterized in that, In step S2, the drying temperature is 110-130℃, and the fluorine content of the polyethersulfone obtained after drying is <1ppm.
8. Polyethersulfone, characterized in that, It is prepared by the method for preparing polyethersulfone as described in any one of claims 1-7.
Citation Information
Patent Citations
A method of synthesizing polyethersulfone resin
CN106565957A
Synthesis method for ternary and multivariant multipolymer polysulfone resin
CN108285535A
Synthetic method for stably improving impact strength of polyethersulfone
CN113881045A
